Perfomance evaluation of task-space controllers for robot manipulator - Wu, Jiang Rong. (2008)
The objective of this project is to study and compare the performance of transpose Jacobian controller and inverse Jacobian controller for set point control and region control using computer simulation. The control laws are simulated under the following three types of uncertainties: · Rotational error from Cartesian coordinates to sensor coordinates · Uncertain kinematics from joint space to Cartesian space · Uncertain gravity in the robot manipulator A Matlab program was developed to simulate the performance of the proposed task-space controllers.